2023
DOI: 10.3390/jof9020243
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Clonally-Related South Asian Clade I Clinical Isolates of Candida auris in a Greek COVID-19 Intensive Care Unit

Abstract: Candida auris has recently emerged as a multidrug-resistant yeast implicated in various healthcare-associated invasive infections and hospital outbreaks. In the current study, we report the first five intensive care unit (ICU) cases affected by C. auris isolates in Greece, during October 2020–January 2022. The ICU of the hospital was converted to a COVID-19 unit on 25 February 2021, during the third wave of COVID-19 in Greece. Identification of the isolates was confirmed by Matrix Assisted Laser Desorption Ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…1 ) within the South Asian lineage (Clade I), similarly to other strains from Greece until today. 7 , 40 Monitoring is ongoing, with new strains being added daily to the Mycology Lab's collection but with no differentiation of the total image until now (same sensitivity profile and phylogeny).…”
Section: Resultsmentioning
confidence: 99%
“…1 ) within the South Asian lineage (Clade I), similarly to other strains from Greece until today. 7 , 40 Monitoring is ongoing, with new strains being added daily to the Mycology Lab's collection but with no differentiation of the total image until now (same sensitivity profile and phylogeny).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies used swabs [48][49][50][51][52][53][55][56][57][58]60,63,65,[68][69][70], while two used gauze [54,59], and one used both direct contact plates and swab techniques [61]. Six studies did not report the methods of sample collection [13,47,62,64,66,67]. Among the studies that employed swabs, only 12 reported the material, of which 9 were sponges [48,55,58,60,63,65,[68][69][70] and 3 were cotton [49,51,53].…”
Section: Potential Hospital Environmental Reservoirsmentioning
confidence: 99%
“…Additionally, 13 studies reported the presence of this yeast in areas outside the patient's rooms, such as keyboards, sinks, and air vents [48,50,[53][54][55][57][58][59][60]64,65,69,70]. The clade of C. auris was determined by WGS and analyzed by fifteen studies, of which twelve studies found the South Asian clade [13,[48][49][50][51][52][55][56][57]62,63,66] and three studies detected the African clade [47,61,64].…”
Section: Potential Hospital Environmental Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical cut-off values for C. auris antifungal susceptibility tests have not yet been reported, it is known that high MICs for some antifungal agents, such as azoles, indicate that these compounds are not a viable therapeutic option for most clinical cases [34]. However, tentative CDC MIC breakpoints have been used for the following antifungal agents: fluconazole (≥32 µg/mL), voriconazole (≥2 µg/mL), posaconazole (≥2 µg/mL), itraconazole (≥2 µg/mL), anidulafungin (≥4 µg/mL), micafungin (≥4 µg/mL), caspofungin (≥4 µg/mL), and amphotericin B (≥2 µg/mL) [87]. According to these breakpoints, around 90% of C. auris isolates in the US are resistant to azoles, 30% are resistant to amphotericin B, and 3-5% are resistant to echinocandins.…”
Section: Antifungal Drug Resistance In C Aurismentioning
confidence: 99%